Branding Higher Education: The Case of Malaysian Higher Education Promotion on the Internet - Alexandra Samokhvalova, (Kajian Malaysia, 2017)
A booming middle class, new attractive study destinations and a resulting shift in student mobility trends have recently established a new dynamic in international higher education. To stay competitive, countries apply marketing strategies to promote and "sell" their higher education to international students-cumcustomers. With the growing use of the Internet to research study destinations, the role of online channels in higher education promotion is becoming increasingly important. The current study investigates the case of Malaysian higher education branding in cyberspace. By applying content analysis to the two major higher education online platforms, this study identifies the core brand values of Malaysian higher education and evaluates their coherence. The research findings demonstrate that both platforms combine nation and higher education branding efforts to create a harmonised image of the national higher education system. Additionally, several suggestions are made concerning the optimisation of the architecture and information presentation of the websites to enhance their attractiveness for users. Finally, the necessity of further investigation into higher education branding for the successful implementation of internationalisation policies in Malaysia is emphasised.